Assistance for Increasing Community Resources Capacity in Implementing Community-Based Tourism Activities in Sukajadi Village, Bogor District - Nisa Rahmaniyah Utami; Wildan Rizky Rahadian; Samuel Samuel (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
The current development of tourism activities has been expanding throughout various regions, particularly in village territories through tourist village development. Essentially, tourism accomplishment in village territories is one of the implementation forms of Community-Based Tourism (CBT) where the community takes part as the executor and object of development. Community-Based Tourism (CBT) is closely related to community empowerment. The method of implementing this activity involves several lecturers and students and community participation in designing these activities. Accompaniment is one of the successful key factors related to community empowerment implementation in terms of achieving Community-Based Tourism (CBT) accomplishment in villages territories.